SUPERVISION IMPLEMENTATION IN MANAGEMENT QUALITY: AN ATTEMPT TO IMPROVE THE QUALITY OF LEARNING AT MADRASAH ALIYAH DARUL A’MAL METRO - Subandi Subandi (Jurnal Pendidikan Islam, 2015)
The primary purpose of this qualitative study is to identify and analyze supervision by implementing management quality to improve the quality of learning at Madrasah Aliyah Darul A’mal Metro, Lampung. The quality of management implementation is elaborated in the steps of assurance of learning quality. Two instruments, which consist of observation and questionnaire, were used in this study of which each instrument was analyzed based the deductive framework. The results of this study from each instrument revealed four steps of assurance of learning quality, among others (1) by socializing academic supervision program and its advantages to all stake holders, and (2) by implementing stages of assurance through academic supervision by the principals of Madrasah Aliyah Darul A’mal and supervisor, (3) performing supervision that is equipped with valid instrument to measure learning success, (4) performing the follow-up program by clinical and group discussion to provide appropriate model of performance.